2013
DOI: 10.1016/j.celrep.2013.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Structure of Stem Cell Growth Factor R-spondin 1 in Complex with the Ectodomain of Its Receptor LGR5

Abstract: Leucine-rich repeat-containing G protein-coupled receptors 4-6 (LGR4-LGR6) are receptors for R-spondins, potent Wnt agonists that exert profound trophic effects on Wnt-driven stem cells compartments. We present crystal structures of a signaling-competent fragment of R-spondin 1 (Rspo1) at a resolution of 2.0 Å and its complex with the LGR5 ectodomain at a resolution of 3.2 Å. Ecto-LGR5 binds Rspo1 at its concave leucine-rich-repeat (LRR) surface, forming a dimeric 2:2 complex. Fully conserved residues on LGR4-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
123
1
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 86 publications
(134 citation statements)
references
References 73 publications
6
123
1
4
Order By: Relevance
“…59 However, binding to the LGR5 induced noticeable changes in the Fu1/Fu2 region, especially in its Ru2 part. Fig.…”
Section: R-spondinmentioning
confidence: 99%
See 4 more Smart Citations
“…59 However, binding to the LGR5 induced noticeable changes in the Fu1/Fu2 region, especially in its Ru2 part. Fig.…”
Section: R-spondinmentioning
confidence: 99%
“…36,39 Structural information is available for the Fu1/Fu2-containing region of Rspo1 (residues 40-127; e.g., see PDB ID: 4BSP). 59 Although longer regions of Rspo1 are typically used in crystallization studies (residues , no coordinates have been determined for their N-(residues 31-39) and C-terminal regions (residues [128][129][130][131][132][133][134][135][136][137][138][139][140][141][142][143][144][145][146]. Recent structural analysis revealed that in its unbound form, the Fu1/Fu2 region of Rspo1 is characterized by the non-equivalent Fu domains, where the Fu1 domain has 3 cysteineknotted b-hairpins, whereas there are 2 such hairpins in the Fu2 domain, with the C-terminal hairpin being missing from the crystal structure, likely due to the high conformational flexibility.…”
Section: R-spondinmentioning
confidence: 99%
See 3 more Smart Citations